Implementasi Model Discovery Learning dalam Mata Pelajaran Al-Qur’an Hadis di Kelas XI Madrasah Aliyah Negeri 3 Banyumas - Hidayat, Maulana; Nurhalim, Muhammad (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The learning of Al-Qur’an and Hadith plays an essential role in shaping students' understanding of the Qur’anic and Hadith content within the school environment. This learning process presents unique challenges for educators, as it is not only aimed at transmitting religious knowledge but also at cultivating moral values, ethics, and spirituality in students’ daily lives, as reflected in the teachings of the Qur’an and hadith. One common issue is the low level of active student participation during the learning process and the difficulty teachers face in fostering learning motivation. As an alternative solution, an active learning approach through the discovery learning model can be implemented. This model provides students with the opportunity to be directly involved in the exploration, discovery, and observation of subject matter. Thus, learners become active participants in the learning process and gain a deeper understanding of content derived from the Qur’an and Hadith. This study aims to analyze the implementation of the discovery learning model in Al-Qur’an hadith instruction at MAN 3 Banyumas. The method used is a qualitative approach through a case study with field research design. The study was conducted at MAN 3 Banyumas, Sumpiuh District. Data collection techniques included observation, interviews, and documentation. The collected data were analyzed through data reduction, data display, and conclusion drawing. To ensure data validity, triangulation techniques were applied. The results showed that the application of the discovery learning model in Al-Qur’an Hadith learning was generally carried out in two main stages: implementation and evaluation. The implementation phase consists of three learning activities introductory, core, and closing activities while the evaluation phase was conducted using both test and non-test instruments